A közalkalmazotti béremelés hatása a tanárok pályaelhagyási döntésére - Júlia Varga (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– The paper investigates teachers' decisions to leave the profession. First we examine the role of earnings and earnings in alternative occupations in these decisions, and then the paper discusses how the public sector wage increase in 2002 has effected exiting decisions of teachers. Using large merged administrative data-sets duration models were estimated. First binary choice Cox proportional hazard models (leaving teaching profession or not), then competing risk models which distinguish exits to another occupation and exits to no-working state. Results show, that earnings matter. Higher wages reduce the probability of exiting teacher profession to go to another occupation or to non-employment. The public sector wage increase has decreased the probability of leaving the teacher profession for inexperienced teachers temporarily, but one or two years after the effect disappeared. For experienced teachers who are older than 51 year-olds the wage increase found to reduce attrition.
Keywords: I22; J28; J31; J45; J62; 330; teacher salaries; teacher attrition; human capital; Vergütungssystem im öffentlichen Dienst; Lehrkräfte; Berufswechsel; Präferenztheorie; Statistische Bestandsanalyse; Ungarn